2018
DOI: 10.1074/jbc.ra118.004889
|View full text |Cite
|
Sign up to set email alerts
|

ATP7A and ATP7B copper transporters have distinct functions in the regulation of neuronal dopamine-β-hydroxylase

Abstract: Edited by Ruma Banerjee The copper (Cu) transporters ATPase copper-transporting alpha (ATP7A) and ATPase copper-transporting beta (ATP7B) are essential for the normal function of the mammalian central nervous system. Inactivation of ATP7A or ATP7B causes the severe neurological disorders, Menkes disease and Wilson disease, respectively. In both diseases, Cu imbalance is associated with abnormal levels of the catecholamine-type neurotransmitters dopamine and norepinephrine. Dopamine is converted to norepinephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 52 publications
(37 reference statements)
0
47
0
1
Order By: Relevance
“…Recent reports have linked copper intracellular availability with intracellular trafficking and secretion of soluble DβH in the human neuroblastoma cell line SH‐SY5Y (Schmidt et al ). The authors used a genetic knockout of ATPase‐dependent copper transporters (ATP7A) or pharmacological intervention using copper chelators (bathocuproine disulfonate and tetrathiomolybdate).…”
Section: Regulation Of Dβh Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have linked copper intracellular availability with intracellular trafficking and secretion of soluble DβH in the human neuroblastoma cell line SH‐SY5Y (Schmidt et al ). The authors used a genetic knockout of ATPase‐dependent copper transporters (ATP7A) or pharmacological intervention using copper chelators (bathocuproine disulfonate and tetrathiomolybdate).…”
Section: Regulation Of Dβh Expressionmentioning
confidence: 99%
“…The authors used a genetic knockout of ATPase‐dependent copper transporters (ATP7A) or pharmacological intervention using copper chelators (bathocuproine disulfonate and tetrathiomolybdate). Both methods resulted in diminished DβH soluble release and reduced intercellular DβH compartment size (Schmidt et al ). The authors also examined the effects of excess copper load by copper chloride (CuCl 2 ); interestingly, this did not alter soluble DβH level or compartment size.…”
Section: Regulation Of Dβh Expressionmentioning
confidence: 99%
“…In the CNS, copper signaling may influence synaptic transmission indirectly by modulating the synthesis of neurotransmitters, e.g., via the peptidylglycine α-amidating monooxygenase (PAM) [ 147 ] and dopamine β-hydroxylase (DBH) [ 148 ] pathways, or directly by being released into the synaptic cleft from the terminals of glutamatergic neurons [ 149 , 150 ]. However, the signal associated with copper ions has a different effect depending on the region where it is released; in the amygdala, copper acts towards enhancement of LTP [ 151 ], while in the hippocampus it shows a tendency to inhibit synaptic plasticity [ 145 ].…”
Section: Coppermentioning
confidence: 99%
“…reported reduced expression and activity of DBH in ATP7B null mice. Again, immunohistochemistry of rat brain sections and cell culture studies by Schmidt et al . revealed that inactivation of ATP7B decreases DBH levels in neurons.…”
Section: Introductionmentioning
confidence: 98%